A STUDY ON THE GROWTH AND PHYSIOLOGICAL RESPONSE OF JUVENILE TINFOIL BARB Barbonymus schwanenfeldii (Bleeker, 1854) UNDER THE INFLUENCE OF pH CHANGES - Oktavia, Nia; Prakoso, Vitas Atmadi; Kamal, Mohammad Mukhlis; Arifin, Otong Zenal; Subagja, Jojo; Kurniawan, Kurniawan; Iswantari, Aliati; Kusmini, Irin Iriana; Irawan, Deni; Cahyanti, Wahyulia; Radona, Deni; Putri, Fera Permata; Bosman, Ofan; Wibowo, Arif; Kristanto, Anang Hari; Gustiano, Rudhy (Agency for Marine and Fisheries Extension and Human Resources, 2024)
Tinfoil barb Barbonymus schwanenfeldii is recognized as one of the potential aquaculture commodities in Indonesia. Nonetheless, lack of data on their environmental tolerance causing this issue to become essential to be investigated. The present study was carried out to assess the pH influence on growth and physiological response of juvenile tinfoil barb. Juvenile tinfoil barbs (TL: 5.5 ± 0.8 cm; BW: 2.4 ± 1.0 g) were treated with four pH level treatments (5, 6, 7, and 8) and three replications with the stocking density of 10 fish each aquarium. Fish were kept for 21 days and fed with commercial fish feed. In this study, pH 8 exposure resulted to lower growth of juvenile tinfoil barb compared to pH treatment 5 to 7 (p<0.05). In terms of survival rate, the results show significantly lower value at pH 8 treatment compared to those of pH 6 and 7 treatment (p<0.05), while it is not significantly different with pH 5 treatment (p>0.05). Additionally, this study found the highest value of glucose, cortisol, and aspartate aminotransferase (AST) on pH 8 treatment (p<0.05). On the other hand, pH 8 exposure led to the lowest creatinine, blood urea nitrogen (BUN), and ALP level (p<0.05). In conclusion, the optimal pH for juvenile tinfoil barb rearing ranged around 6-7.